2018
DOI: 10.4028/www.scientific.net/msf.941.851
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Magnesium and Magnesium Alloy Machine Chips Using High-Pressure Torsion

Abstract: The high-pressure torsion processing technique was used to consolidate and process magnesium-based chips. Chips were prepared by machining commercially pure magnesium and a magnesium alloy AZ91 separately. Optical microscopy and microhardness measurements showed good consolidation of pure magnesium. The magnesium alloy continued to exhibit the boundaries between the chips even after 5 turns of HPT suggesting poor bonding. The results show that soft chips are easier to consolidate through HPT than harder alloys. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Composites with similar amount of hard quasicrystal particles could be consolidated by 10 turns of HPT using pure magnesium as matrix material but not with AZ91. It is worth noting that previous studies have shown that pure magnesium chips, pure or with the addition of alumina particles, could be consolidated after 5 turns of HPT [11,16]. On the other hand, machining chips of AZ91 were not consolidated in the same conditions [16].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Composites with similar amount of hard quasicrystal particles could be consolidated by 10 turns of HPT using pure magnesium as matrix material but not with AZ91. It is worth noting that previous studies have shown that pure magnesium chips, pure or with the addition of alumina particles, could be consolidated after 5 turns of HPT [11,16]. On the other hand, machining chips of AZ91 were not consolidated in the same conditions [16].…”
Section: Discussionmentioning
confidence: 87%
“…It is worth noting that previous studies have shown that pure magnesium chips, pure or with the addition of alumina particles, could be consolidated after 5 turns of HPT [11,16]. On the other hand, machining chips of AZ91 were not consolidated in the same conditions [16]. Also, a recent paper showed the lack of consolidation of an AZ91-Bioactive Glass composite even after 50 turns of HPT [13].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effectiveness of the route depends on the nature of the materials being mixed. It has been shown that pure magnesium machining chips can be fully consolidated after 5 turns of HPT while the boundaries between the original chips of the magnesium alloy AZ91 are still visible after the same number of turns [20].…”
Section: Processingmentioning
confidence: 99%
“…The number of phases and their distribution in the microstructure depends upon the number of materials used in the mixing, the volume fraction of each material and their original size. Thus, the processing of particles of pure magnesium, without any additional phase, leads to a single phase disc after sufficient number of turns when the material is observed using optical microscopy [20]. It is, however, expected that the oxide layer of the original particles will be dispersed within the metallic matrix after consolidation.…”
Section: Microstructurementioning
confidence: 99%